Correlation of Tinnitus Severity Index and Tinnitus Handicap Inventory with Hematological Parameters in Patients with Subjective Tinnitus - Yazici, Demet; Cihan, Mehmet Celalettin (International Archives of Otorhinolaryngology, 2023)
Introduction Tinnitus etiopathogenesis is still unclear and treatment options are controversial despite current advances in medicine.Objectives To analyze the correlation between patients' symptom scores, systemic inflammation, and trombosis biomarkers.Methods In this prospective study, we evaluated the degree of complaints of subjective tinnitus patients with the tinnitus severity index (TSI) and tinnitus handicap inventory (THI), and correlated these symptom scores with hematological parameters such as the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), mean thrombocyte volume (MPV), and platelet distribution width (PDW).Results A total of 44 patients with subjective tinnitus, 25 (56.8%) men and 19 (43.2%) women, were included in this study. The mean age of the patients was 42.3 ± 14.8 years. When the correlation between TSI and NLR, PLR, PDW, and MPV values of the patients were analyzed, no statistically significant correlation was found between TSI, NLR, and PLR (p > 0.05). However, there was a statistically weak positive correlation between TSI, MPV, and PDW.(p < 0.05). When the correlation between THI and NLR, PLR, PDW, and MPV values of the patients were analyzed, no statistically significant correlation was found between THI, NLR, and PLR (p > 0.05). There was a statistically weak positive correlation between THI, MPV, and PDW (p < 0.05).Conclusion We were unable to detect any relationship between systemic inflammation markers (NLR and PLR) and symptom scores, but a weakly positive correlation was observed between thrombosis markers (MPV and PDW) and symptom scores, and as the subclinical thrombosis markers elevated, so did the symptom scores.
Keywords: tinnitus; subjective tinnitus; correlation; inflammation; thrombosis